Two Improved Cancellation Techniques for Direct-Conversion Receivers. (30th August 2016) - Hao, Xueyuan; Yan, Xiaohong
Abstract : To solve the problems of carrier leakage and DC offset in direct-conversion receiver (DCR) system, the paper proposed two kinds of improved technology to overcome the problems in DCR system. One is the RF carrier cancellation technology; the traditional cancellation technology based on lumped parameter filter can be easily influenced by distribution parameters, the improved circuits use a 3 db bridge to realize a 180-degree phase shifter, and the method can adapt to a wider range of RF frequency. Another is DC offset cancellation technique; a novel DC servo loop circuit is proposed to replace the traditional AC-coupled amplifier circuit. It can improve the integrity of the baseband signal and reduces the complexity of the subsequent software algorithm. Experimental results show that two kinds of improved technology can improve the performance of DCR and expand its scope of application.